Dictogloss steals the show? Productive use of formulaic sequences by advanced learners - Magdalena Zinkgraf; María Angélica Verdú (Lexis: Journal in English Lexicology)
Corpus studies into the nature of language and the interrelationship between grammar and lexis have highlighted the pervasiveness of recurrent strings of words essential to the construction of meaning which Wray [2002: 9] has named “formulaic sequences” (FS). Research by Boers et al [2006], Eyckmans [2007], Stengers [2009] and Wray & Fitzpatrick [2008] suggests that good command of these phrases in the foreign language (FL), of their typical occurrence and of their use restrictions contributes to learners’ fluency, and is taken as evidence of a high level of proficiency. Boers & Lindstromberg [2012] argue that explicit FS instruction accompanied by awareness-raising tasks yield significant learning gains, especially in FL contexts. As a pushed-output procedure, Wajnryb’s dictogloss technique [1990] has recently been adapted in FS-focused instruction studies like those of Janssens [2016] and Lindstromberg, Eyckmans & Connabeer [2016]. In similar fashion, we designed an experimental study for the teaching of nine pedagogically relevant sequences with Spanish-L1 EFL university learners. Two types of treatment were implemented with a focus on the target FSs’ meanings, forms and uses with two naturally-occurring learner groups (Group 1, N=13, and Group 2, N=17), whose performance was compared to that of a control group (N=7). Group 1 completed a set of Focus-on-Form activities [Doughty & Williams 1998], while Group 2 carried out two sessions of FS-oriented dictogloss. Results show that learners in Group 2 produced 40 instances of the target FS in five essay-writing tasks at different stages of the study and as late as a month and a half post intervention. By contrast, Group 1 produced 23 instances of seven target FSs across three essay writing tasks, six weeks after treatment. These findings indicate that dictogloss seems to reinforce advanced students’ familiarization with target FS in context, and FS memory retention over time. Based on the descriptive analysis of uncued target FSs produced by learners in their written production tasks, the possible contributions of dictogloss to long-term FS acquisition are discussed.